Expanding the spectrum of clinical severity of AICA‐ribosiduria: Report of two siblings with mild phenotype caused by a novel pathogenic variant in ATIC gene - Galli, Jessica; Valente, Enza Maria; Dewulf, Joseph; Franzoni, Alessandra; Marie, Sandrine; Plumari, Massimo; Zanetti, Federica; Fazzi, Elisa (American journal of medical genetics. Part A, 2023)
5‐Amino‐4‐imidazolecarboxamide‐ribosiduria (AICA‐ribosiduria) is an extremely rare inborn error of purine biosynthesis metabolism caused by pathogenic variants in ATIC gene that encodes a protein catalyzing the last steps of the de novo purine biosynthesis. To date, only six cases have been reported presenting a severe phenotype characterized by coarse facies and variable dysmorphic features, intrauterine and postnatal growth retardation, severe and early neurodevelopment delay, profound congenital visual deficit, scoliosis and, less frequently, epilepsy, aortic coarctation, chronic hepatic cytolysis, nephrocalcinosis and mild genitalia malformation. In this article, we report two new cases of AICA‐ribosiduria carrying new pathogenic variants in ATIC (c.421C>T;p.Arg141Ter and c.1753A>G p.Thr585Ala) associated to a milder phenotype compared to previously reported patients. Particularly, the children showed few dysmorphic features (bulging forehead, depressed nasal bridge, and flat nasal tip), postnatal growth impairment, psychomotor delay since the second year of life, reduction of visual acuity (from mild impairment to low vision from the age of 5 years and to partial blindness from the age of 7 years) and mild hepatic dysfunctions. Scoliosis as well as epilepsy, renal involvement, or genitalia malformation were not detected. According to literature data, we found an abnormal accumulation of intermediates of de novo purine biosynthesis in the urine of both siblings. This report expands the spectrum of phenotypic severity associated to ATIC biallelic pathogenic variants and prompts the need to investigate ultra‐rare causes of metabolic disorders such as AICA‐ribosiduria in subjects with early neurological and sensory involvement of uncertain etiology.